1989
DOI: 10.3109/08880018909034274
|View full text |Cite
|
Sign up to set email alerts
|

Committed Erythroid Progenitors and Erythropoietin Levels in Anemic Children with Lymphomas and Tumors

Abstract: In order to investigate the pathogenesis of anemia in childhood malignancy, we studied erythroid cell proliferation responses with bone marrow erythroid cultures and serum erythropoietin (Ep) levels in 32 children with lymphomas and malignant tumors. The erythroid colony formation from 20 normal controls (mean 68.8 colony-forming-unit erythroid [CFU-E] and 32 burst-forming-unit erythroid [BFU-E] derived colonies/10(5) mononuclear cells), was higher than that seen in children with lymphomas (mean 45.9 CFU-E and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Because TfR expression is upregulated when a cell needs more iron and sTfR is proportional to total TfR, concentrations of TfR are increased in the plasma or serum of an iron-deficient subject (6). The increased sTfR concentration observed in patients with iron-deficient erythropoiesis reflects the abundant erythroid precursor expression (7). However, other conditions associated with erythroid hyperplasia, such as β-thalassemia (8) and autoimmune hemolytic anemia (9), also increase the sTfR concentration, suggesting that a high value will not always be specific for iron deficiency (10).…”
mentioning
confidence: 99%
“…Because TfR expression is upregulated when a cell needs more iron and sTfR is proportional to total TfR, concentrations of TfR are increased in the plasma or serum of an iron-deficient subject (6). The increased sTfR concentration observed in patients with iron-deficient erythropoiesis reflects the abundant erythroid precursor expression (7). However, other conditions associated with erythroid hyperplasia, such as β-thalassemia (8) and autoimmune hemolytic anemia (9), also increase the sTfR concentration, suggesting that a high value will not always be specific for iron deficiency (10).…”
mentioning
confidence: 99%
“…Decreased EPO production by the renal tubular cells is a significant cause of CAA in patients receiving nephrotoxic chemotherapy, such as cisplatin for children with solid tumor malignancies. For reasons that are as yet unclear, EPO production in some patients with cancer is inadequate relative to the degree of anemia, and this is unrelated to renal impairment [16,17].…”
Section: Decreased Production Of Epomentioning
confidence: 99%
“…The pathophysiology of this type of anaemia is multifactorial but the ACD plays a major role. The ACD is a cytokine‐mediated, normochromic/normocytic anaemia characterized by reticulocytopenia, hypoferraemia in the presence of adequate iron stores and a shortened erythrocyte survival of approximately 60–90 d. Cytokines such as tumour necrosis factor, interferon‐γ and interleukin‐1 inhibit erythropoiesis both directly by suppressing erythroid colony growth (Kalmanti & Kalmanti, 1989) and indirectly by suppressing erythropoietin production. This latter observation was supported by Miller et al (1990) who demonstrated the relative decrease in erythropoietin production that occurs in patients with malignant disease by contrasting serum erythropoietin levels in patients with iron deficiency anaemia with the levels in patients with a variety of cancerous illnesses.…”
Section: Introductionmentioning
confidence: 99%